2023
DOI: 10.1002/jcaf.22664
|View full text |Cite
|
Sign up to set email alerts
|

The bridge to quality financial reporting: Audit committees’ mediating role in IFRS implementation for emerging markets

Ines Kateb

Abstract: This study aims to examine the impact of International Financial Reporting Standards (IFRS) adoption on financial reporting quality in Saudi Arabia, with a specific focus on the mediating role of effective audit committees (ACs) and the specific characteristics of ACs that have a negative correlation with earnings management (EM) practices. The research collected financial data from 92 listed firms spanning the period from 2012 to 2020 encompassing both the years  before and after the IFRS adoption in 2017. . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 99 publications
(257 reference statements)
0
6
1
Order By: Relevance
“…Although the findings of the study contradict the literature that indicates IFRS negatively affect financial performance FP (Major & Marques, 2009;Nepal & Deb, 2023), many contend that such relationship is insignificant and unclear (Păşcan & Ţurcaş, 2012;Ofoegbu & Odoemelam, 2018). The findings of the study can be justified by agency theory, which suggests that the IFRS enhances the corporate governance measures (Kateb, 2023), which per se results in the better FP. Thus, our findings demonstrate that developing economies, following the traditional GAAP-based standards, can be significantly benefited by transitioning to IFRS.…”
Section: Discussioncontrasting
confidence: 72%
“…Although the findings of the study contradict the literature that indicates IFRS negatively affect financial performance FP (Major & Marques, 2009;Nepal & Deb, 2023), many contend that such relationship is insignificant and unclear (Păşcan & Ţurcaş, 2012;Ofoegbu & Odoemelam, 2018). The findings of the study can be justified by agency theory, which suggests that the IFRS enhances the corporate governance measures (Kateb, 2023), which per se results in the better FP. Thus, our findings demonstrate that developing economies, following the traditional GAAP-based standards, can be significantly benefited by transitioning to IFRS.…”
Section: Discussioncontrasting
confidence: 72%
“…Another study found no significant relationship between the adoption of IFRS and share price and EPS as components of price value relevance (Kumaravel, 2022). Also, a study on emerging markets (EM) found that IFRS adoption has a negative and significant impact on EM practices (Kateb, 2023). Therefore, it can be concluded that the relationship between IFRS adoption and CG is complex and may vary depending on the context and the specific factors involved.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the impact of EM on RL within Saudi non-financial firms, we use DACC as a proxy for EM and use the performance matched model (PMM) outlined by Kothari et al (2005). This model is preferred due to its theoretical relevance in analyzing EM, as well as its empirical robustness, evidenced by studies in similar contexts (Gerged et al, 2020;Kateb, 2024;Kateb and Youssef, 2023;Habbash and Alghamdi, 2017;Almarayeh et al, 2024). Unlike traditional models like the Jones (1991) Model and the Modified Jones Model (Dechow et al, 1995), PMM incorporates firms' financial performance, facilitating a more accurate detection of DACC by considering performance variations over time.…”
Section: Ijaim 324mentioning
confidence: 99%
“…Empirical research has a notable gap in examining the impact of IFRS implementation on the relationship between relevance and reliability of financial reporting, especially in emerging markets and GCC countries, with exceptions like the studies by Kateb (2024) and IJAIM 32,4 Alruwaili et al (2023). Kateb's research revealed a decline in EM after the adoption of IFRS in 2017 among listed companies in Saudi Arabia, highlighting the initial effects of IFRS adoption on financial reporting practices.…”
Section: Introductionmentioning
confidence: 99%